Artificial intelligence in health : first International Workshop, AIH 2018, Stockholm, Sweden, July 13-14, 2018, Revised selected papers /: first International Workshop, AIH 2018, Stockholm, Sweden, July 13-14, 2018, Revised selected papers. (2019) - Unknown
No abstract available